Embryonic development of fin spines in Callorhinchus milii (Holocephali); implications for chondrichthyan fin spine evolution. Issue 6 (7th November 2014) - Jerve, Anna; Johanson, Zerina; Ahlberg, Per; Boisvert, Catherine
SUMMARY Fin spines are commonly known from fossil gnathostomes (jawed vertebrates) and are usually associated with paired and unpaired fins. They are less common among extant gnathostomes, being restricted to the median fins of certain chondrichthyans (cartilaginous fish), including chimaerids (elephant sharks) and neoselachians (sharks, skates, and rays). Fin spine growth is of great interest and relevance but few studies have considered their evolution and development. We investigated the development of the fin spine of the chimaerid Callorhinchus milii using stained histological sections from a series of larval, hatchling, and adult individuals. The lamellar trunk dentine of the Callorhinchus spine first condenses within the mesenchyme, rather than at the contact surface between mesenchyme and epithelium, in a manner more comparable to dermal bone formation than to normal odontode development. Trabecular dentine forms a small component of the spine under the keel; it is covered externally with a thin layer of lamellar trunk dentine, which is difficult to distinguish in sectioned adult spines. We suggest that the distinctive characteristics of the trunk dentine may reflect an origin through co‐option of developmental processes involved in dermal bone formation. Comparison with extant Squalus and a range of fossil chondrichthyans shows that Callorhinchus is more representative than Squalus of generalized chondrichthyan fin‐spine architecture, highlighting its value as a developmental model organism.